Nrf2-peroxiredoxin I axis in polymorphous adenocarcinoma is associated with low matrix metalloproteinase 2 level - Brod, J. M.; Dias Demasi, Ana Paula; Montalli, V. A.; Teixeira, L. N.; Furuse, C. [UNESP]; Aguiar, M. C.; Soares, A. B.; Sperandio, M.; Araujo, V. C. (Springer, 2017)
Polymorphous adenocarcinoma (PAC) is a malignant epithelial neoplasm that affects almost exclusively the minor salivary glands, generally described as having a relatively good prognosis. Aberrant nuclear factor erythroid 2 (NF-E2)-related factor (Nrf2) activation in tumor cells has been associated with induction of antioxidant enzymes, such as peroxiredoxin I (Prx I) and increased matrix metalloproteinase (MMP) expression. In this context, the aim of the present study was to evaluate the expression of Nrf2 and correlate it with Prx I and MMP-2 secretion in PAC. Thirty-one cases of PAC from oral biopsies were selected and immunohistochemically analyzed for Nrf2 and Prx I. MMP-2 quantification was performed on primary cell cultures derived from PAC. Oral squamous cell carcinoma (OSCC) cell cultures were used as control. A high immunoexpression of Nrf2 was observed in both the cytoplasm and the nucleus of neoplastic cells from PAC. Nuclear staining for Nrf2 suggested its activation in the majority of the PAC cells, which was confirmed by the high expression of its target gene, Prx I. Quantification of MMP-2 secretion showed lower levels in PAC cell cultures when compared to OSCC cell cultures (p < 0.05). In conclusion, although Nrf2 overexpression has been frequently associated with high-grade malignancies, such relationship is not infallible and, in fact, the opposite may occur in low-grade tumors, such as PAC of minor salivary glands.
Keywords: Polymorphous adenocarcinoma; Salivary gland; Nrf2; Peroxiredoxins; Matrix metalloproteinases